Analysis of Raft or Pile Foundation of any Building or Structure: Analyzing the Impact of Piled-Raft Foundations on High-Rise Structures (Journal of Advances and Scholarly Researches in Allied Education, 2021)
High-rise structures may benefit from piled-raft foundations instead of standard pile or mat foundations. Pinned Rift Foundations are designed to be strong enough to hold the applied loads with an adequate factor of safety, while allowing for acceptable settlements at working load. Many studies have examined the behavior of pile raft foundations, including the impact of pile length, pile distance, pile arrangement, and cap thickness under static and dynamic loads that may be applied vertically or horizontally. Pile length combinations are examined in this study to determine how multi-story buildings respond to vertical loads. Soil settlements are assumed to be zero, and foundation settlements are calculated assuming a flexible structure. It is possible, however, that the structure's stiffness will limit any movement of its foundations, and even small differences in settlement would modify the structural elements' forces. This means that the actual behavior of a building is greatly altered by the interaction of the structure with its foundations and the soil medium underneath the foundations. Finite element software was used in this study to investigate the interaction between piles and soil structures. In ANSYS 11, This study discusses the importance of soil structure interaction in the performance of a structure, which has been proven to have a major impact.